Inuit Youth Transitioning out of Residential Care: Obstacles to Re-integration and Challenges to Wellness - Fraser, Sarah L.; Vachon, Mélanie; Arauz, Maria J.; Rousseau, Cécile; Kirmayer, Laurence J. (First Peoples Child & Family Review, 2012)
For youth under child welfare, transitioning out of residential care and reintegrating into their community can be a difficult process. This may be especially true for Inuit youth who, because they are away from their communities, cannot develop networks and relationships that would provide a secure place for their development as an adult and as a community member. The objectives of this study were to document how transition out of care is addressed in a residence specialized for Inuit youth under government care, and to explore, from the perspective of residential managers and staff, what factors facilitate or create obstacles to successful transition. Interviews were conducted to discuss the transition of 11 youth from residential placement back into communities. The criteria used by managers and staff to describe transitions mostly focused on the behaviours of the youth and the ability to create and implement a plan. Are current theme was the importance of continuity and connections with family, staff, and culture. Various measures were put into place around the current system of care in order to facilitate continuity and connections to respond to the cultural and personal needs of youth. To enhance the “cultural competence” of care, we suggest that: (i) criteria for successful and unsuccessful transitions be determined with youth, families, and communities; (ii) that Inuit representation in care be increased; and (iii) that measures be taken outside the current system of care to encourage shifts in power distribution.